TERAPAN FUNGSI DENSITAS EMPIRIK DENGAN PENDEKATAN DERET FOURIER UNTUK ESTIMASI DIAGRAM PENGENDALI KUALITAS - Santoso, Rukun (MATEMATIKA, 2007)
Any continues function on the Hilbert space L2[-p,p] can be represented as Fourier series. By this fact, a density function can be estimated by Fourier series as estimator of continues function on L2[-p,p]. Further, this function estimator will be used to derive process parameters that needed on the control quality chart design Â